Nursing Care In Breast Cancer Patients With The Virginia Henderson Model Theory Approach - Samran Samran; Irna Nursanti (Faculty of Medicine, Universitas Tadulako, 2026)
Background: Nursing theory underpins professional nursing practice by providing systematic frameworks for care delivery. Among conceptual models, Virginia Henderson’s nursing theory emphasizes 14 basic human needs that guide comprehensive, patient-centered nursing care. This model is particularly relevant for patients with breast cancer, who experience complex physical and psychosocial problems. Objective: This case study aimed to implement nursing care for a breast cancer patient using the Virginia Henderson nursing model as a theoretical approach. Methods: A descriptive case study design was applied. The subject consisted of one patient diagnosed with breast cancer. Data were collected through the nursing process, including comprehensive assessment, nursing diagnosis formulation, planning of interventions, implementation of nursing actions, and systematic evaluation. Results: The evaluation showed that nursing diagnoses of acute pain and risk of infection were partially resolved and required ongoing interventions, whereas the diagnosis of impaired physical mobility was successfully resolved following nursing care based on Henderson’s model. The structured focus on basic needs facilitated individualized interventions and continuity of care. Conclusion: The application of the Virginia Henderson nursing model reduced pain, infection risk, and mobility limitations, supporting its use as an evidence-based framework for nursing care in breast cancer patients in clinical practice.